Gonopodial system review and a new fish record of Poeciliopsis infans (Cyprinodontiformes: Poeciliidae) for Lake Patzcuaro, Michoacan, central Mexico - Galindo-Villegas, Jorge (2002)
Since 1997, Poeciliopsis infans Woolman 1894 has been recognized as a new inhabitant of Lake Patzcuaro, Michoacan in Central Mexico. Between February 1997 and October 1998, nine fish samples were collected at Lake Patzcuaro. Morphometric and meristic counts were conducted on a random selection of 40 organisms of both sexes of Poeciliopsis infans. Males of these viviparous fish posses a modified anal fin called gonopodium. The characteristic hemal spine on the 18th caudal vertebra for this species is described herein and the bony components of the gonopodial structure and suspensoria that together comprise the gonopodial system, which is important for taxonomic studies at various levels of classification were reviewed. Poeciliopsis infans displays a high degree of sexual dimorphism in body shape and anal fin anatomy with the most conspicuous difference observed in anal fin height, which averages 40% of Sl in males and 17% in females. Comparisons between male and female anal fins are described herein as well as the possible impacts of this species on Lake Patzcuaro fish fauna.